Good Governance, Performance Based Budgeting and SKPD Budget Quality SKPD (The Case of A Structural Model Approach) - Devie Octariani; Akram Akram; Animah Animah (Magister Ilmu Administrasi Publik, 2017)
The aims of this study are to examine and analyze the influence of implementing good governance and performance based budgeting on the quality of budgets of local government offices (SKPD). This research used analytical techniques that included Partial Least Square (smartPLS) 3.0, while goal setting theory was used in o explaining the phenomenon of budget qualities. The population of the study was all SKPDs in Sumbawa Regency. Meanwhile, 94 respondents, who were selected using purposive sampling method served as respondents. The inclusion of SKPD was conditional on it having been examined for compliance with service quality considerations by Ombudsman in 2015. Data was collected using the questionnaire technique. The results of this study showed that the implementation of good governance and performance based budgeting through district contributes to improvement in budget quality. The implications of this study is that local governments should implement principles of good governance and performance based budgeting they aim to improve the quality of public services they deliver.